Contesting anticipatory regimes in education: exploring alternative educational orientations to the future - Amsler, Sarah; Facer, Keri (Elsevier, 2017)
Advanced capitalist societies are characterized by three forms of power and powerlessness: a hegemony of political monoculture; the ‘undoing’ of democratic forms of political agency and subjects; and the ‘political construction of hopelessness’ in challenging these structural foreclosures and ideological consensus. In this context, how can learning enable collective survival in the present and enlarge possibilities for yet-unimaginable alternative futures to emerge? This paper explores this question by juxtaposing three models of educational futurity in different neoliberal contexts. The first, dominating state education policy and practice in Anglospheric and specifically British institutions, promotes performative and disciplinary regimes of anticipation. The second, circulating in discourse and in experimental spaces within this hegemonic context, advocates an emergentist, critical and creative relationship to the future. The third, which thrives in the margins and relative exteriorities of the capitalist world system, promotes an ecological, epistemically disobedient and utopian mode of anticipatory consciousness which ‘projects emancipation beyond the constraints of the existing discourse’ of colonial modernity. We do not attempt to compare these different contexts and models in this paper, but to read each for its difference to illustrate that modes of anticipation in education influence the construction of hopelessness and hope by shaping what is learned about the nature of political possibility and the relationship between learning and the future. We argue that pedagogies which embrace critical modes of anticipation offer alternatives to contemporary regimes of anticipation in education in Britain today.